Fermentative capacity of baker’s yeast exposed to hyperbaric stress - Campelo, Ana F. (2004)
Baker’s yeast suspensions were incubated at different pressures (from 1 bar to 6 bar) and different gases [air, O2 and a mixture of 8% (v/v) CO2, 21% O2 and N2]. Raising the air pressure from 1 bar to 6 bar stimulated cell growth but had no effect on leavening ability or viability of the cells. A 50% reduction of the CO2 produced in dough occurred with 6 bar O2 which also stopped growth. The fermentative capacity of the cells was stimulated by the cells exposure to increased CO2 partial pressure up to 0.48 bar.